Exploring the role of morphology in the evolution of Spanish - Rini, Joel (John Benjamins Pub., 1999)
After a brief survey of the perception of morphological change in the standard works of the Hispanic tradition in the 20th century, the author first attempts to refine concepts such as analogy, leveling, blending, contamination, etc. as they have been applied to Spanish. He then revisits difficult problems of Spanish historical grammar and explores the extent to which various types of morphological processes may have operated in a given change. Selected problems are examined in light of abundant textual evidence. Some include: the resistance to change of Sp. dormir 'to sleep', morir 'to die'.
Keywords: Spanish language -- Grammar, Historical.; Spanish language -- Morphology.; Espagnol (Langue) -- Grammaire historique.; Espagnol (Langue) -- Morphologie.; Spanish language -- Grammar, Historical; Spanish language -- Morphology; Diachronische morfologie.; Historische grammatica.; Spaans.; Electronic book.